Hubungan Dukungan Suami Dengan Kecemasan Peran Baru Sebagai Ibu Remaja Post Section Caesarea - Rahayu, Meidita Siwityas; Dr. Eny Purwandari, M.Si, Dr. Eny Purwandari, M.Si (2016)
Risk arises psychological mental strain and confusion regarding the role of social change of a person teen girl became pregnant and become a mother. It is necessary for the support given from the husband in order to simplify and ease the psychological burden of a wife for a new role of a teenage mother in the care of children and families. This study aims to determine whether there is a relationship between husband support the new role of teenage mothers anxiety Post Section Caesarea in RSUI Kustati Surakarta. The hypothesis proposed that there is a negative relationship between husband support the new role of teenage mothers anxiety Post Saction Caesarea RSUI Kustati Surakarta. The subjects of this study are patients with postpartum during the period 1 to 7 days in RSUI Kustati Surakarta totaling 80 slubyek. Sampling using incidental sampling, data collection method using scales and questionnaires that Likert scale questionnaire Hars. Methods of data analysis using product moment analysis techniques. The results showed a negative relationship exists but was not significant between husband support the new role of teenage mothers anxiety post sectio caesarea. Effective contribution to anxiety husband support the new role of teenage mothers was 1,79%,, indicated by the correlation coefficient ( r2) of 0,0179, indicating that very little, in the presence of other factors namely the social culture, especially mothers.